Management of leaf spot of turmeric (Curcuma longa L.) caused by Colletotrichum capsici through fungicides - V P Pandey, R S Mishra (Journal of Spices and Aromatic Crops, 2015)
An experiment was conducted to evaluate the efficacy of four fungicides viz., hexaconazole (0.1%), propiconazole (0.1%), tricyclazole (0.1%) and carbendazim + mancozeb (0.1%) for the management of leaf spot disease of turmeric through rhizome treatment + foliar spray and foliar spray alone at 45 and 90 days after planting (DAP). Rhizome treatment with carbendazim + mancozeb gave the best results for rhizome germination (91.13%) followed by propiconazole (88.40%) and hexaconazole (87.33%). Foliar application of propiconazole (0.1%) at 45 and 90 DAP was significantly superior in minimizing percent disease intensity (27.61) with increased fresh rhizome yield (33.96 - 34.33 t ha-1). C:B ratio was the highest (1:2.65) with foliar spray of propiconazole.